Cost-effectiveness of broadly neutralizing antibodies for HIV prophylaxis for infants born in settings with high HIV burdens - Christopher Alba; Shelly Malhotra; Stephanie Horsfall; Matthew E. Barnhart; Adrie Bekker; Katerina Chapman; Coleen K. Cunningham; Patricia E. Fast; Genevieve G. Fouda; Kenneth A. Freedberg; Ameena Goga; Lusine R. Ghazaryan; et al. (PLoS ONE, 2025)
Background Approximately 130 000 infants acquire HIV annually despite global maternal antiretroviral therapy scale-up. We evaluated the potential clinical impact and cost-effectiveness of offering long-acting, anti-HIV broadly neutralizing antibody (bNAb) prophylaxis to infants in three distinct settings. Methods We simulated infants in Côte d’Ivoire, South Africa, and Zimbabwe using the Cost-Effectiveness of Preventing AIDS Complications-Pediatric (CEPAC-P) model. We modeled strategies offering a three-bNAb combination in addition to WHO-recommended standard-of-care oral prophylaxis to infants: a) with known, WHO-defined high-risk HIV exposure at birth (HR-HIVE); b) with known HIV exposure at birth (HIVE); or c) with or without known HIV exposure (ALL). Modeled infants received 1-dose, 2-doses, or Extended (every 3 months through 18 months) bNAb dosing. Base case model inputs included 70% bNAb efficacy (sensitivity analysis range: 10–100%), 3-month efficacy duration/dosing interval (1–6 months), and $20/dose cost ($5–$100/dose). Outcomes included pediatric HIV infections, life expectancy, lifetime HIV-related costs, and incremental cost-effectiveness ratios (ICERs, in US$/year-of-life-saved [YLS], assuming a ≤ 50% GDP per capita cost-effectiveness threshold). Findings The base case model projects that bNAb strategies targeting HIVE and ALL infants would prevent 7–26% and 10–42% additional pediatric HIV infections, respectively, compared to standard-of-care alone, ranging by dosing approach. HIVE-Extended would be cost-effective (cost-saving compared to standard-of-care) in Côte d’Ivoire and Zimbabwe; ALL-Extended would be cost-effective in South Africa (ICER: $882/YLS). BNAb strategies targeting HR-HIVE infants would result in greater lifetime costs and smaller life expectancy gains than HIVE-Extended. Throughout most bNAb efficacies and costs evaluated in sensitivity analyses, targeting HIVE infants would be cost-effective in Côte d’Ivoire and Zimbabwe, and targeting ALL infants would be cost-effective in South Africa. Interpretation Adding long-acting bNAbs to current standard-of-care prophylaxis would be cost-effective, assuming plausible efficacies and costs. The cost-effective target population would vary by setting, largely driven by maternal antenatal HIV prevalence and postpartum incidence.